Highly swelling, tough intelligent self-healing hydrogel with body temperature-response. (5th November 2020) - Chen, Yang; Liu, Tao; Wang, Guoyin; Liu, Jianzhi; Zhao, Ling; Yu, Yueqin
Graphical abstract: Highlights: Combine excellent mechanical properties with effective self-healing properties. The LCST is close to the body temperature. The novel design of dynamic reversible chemical bonds. Hydrogels were prepared by one-step synthesis method. Abstract: Achieving hydrogels with mechanical and self-healing properties is highly desirable for their expanding applications, yet remains an ongoing challenge. The synergistic design of dynamic reversible chemical bond opens a new research direction for this material. Herein, a molecular design strategy is proposed via dynamic reversible ionic bond formed between amino and sulfonic acid groups endow self-healing properties for hydrogels while introducing the N -isopropylacrylamide (NIPAm) crosslinked network realized the strength property including high compressive strength and high ductility, and intrinsic temperature sensitivity due to its unique amphiphilic structure for water. By adjusting the mass ratios of NIPAm, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and chitosan (CS), the optimal synthesis conditions for the P(AMPS-NIPAm)/CS hydrogel were obtained. Importantly, this intelligent P(AMPS-NIPAm)/CS hydrogel reveals a successful balance between mechanical and self-healing properties into advanced materials. The self-healing efficiency is as high as 98.51%. Furthermore, the lower critical solution temperature (LCST) of sample AMPS/CS-1.4:1 is 37 ℃, which is closest to the human body temperature. These characteristics open a novel pathway to intelligent self-healing hydrogels in terms of drug delivery and wound dressings.